Effect of eliminating chronic diseases among elderly individuals - Alessandro Goncalves Campolina; Fernando Adami; Jair Licio Ferreira Santos; Maria Lucia Lebrao (Universidade de São Paulo, 2013)
OBJECTIVE: To determine whether the elimination of certain chronic diseases is capable of leading to the compression of morbidity among elderly individuals. METHODS: A population-based, cross-sectional study was carried out with official data for the city of Sao Paulo, Southeastern Brazil in 2000 and data from the SABE (Health, Wellbeing and Ageing) study. Sullivan's method was used to calculate disability-free life expectancy. Cause-deleted life tables were used to calculate the probabilities of death and disabilities with the elimination of health conditions. RESULTS: The largest gains in disability-free life expectancy, with the elimination of chronic illness, occurred in the female gender. Among individuals of a more advanced age, gains in disability-free life expectancy occurred as result of a relative compression of morbidity. Among men aged 75 years, all conditions studied, except heart disease and systemic arterial pressure, led to an absolute expansion of morbidity and, at the same time, to a relative compression of morbidity upon being eliminated. CONCLUSIONS: The elimination of chronic diseases in the elderly could lead to the compression of morbidity in elderly men and women.